Noncommutative deformation and a topological nature of Koiter singularity - Khoa, Trinh Van (Vietnam Journal of Mechanics, 2005)
In this paper we constructed the model of noncommutative plastic deformation and give the proof of Koiter hypothesis. We showed, that the occurrence of Koiter singularity has topological reasons and the number of Koiter singularities - is the topological Pontriagin number.